2020
DOI: 10.1111/bjhp.12452
|View full text |Cite
|
Sign up to set email alerts
|

Habits and self‐efficacy moderate the effects of intentions and planning on physical activity

Abstract: Objectives. Behavioural intentions as well as action planning can facilitate the adoption and maintenance of physical activity under certain conditions. The present study examined levels of plan-specific self-efficacy and habit strength as possible conditions that may modify this relationship.Design. As a secondary analysis of a larger randomized trial to improve physical activity, n = 225 recipients of a planning intervention were followed up at five measurement points over one year.Methods. Two-level models … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Interestingly, automatic motivation was negatively associated with both PA for transport and PA at work and not associated with the other PA modalities. Though automatic processes can be influential on PA (Di Maio, Keller, Hohl, Schwarzer, & Knoll, 2020;Kaushal, Rhodes, Meldrum, & Spence, 2017;Rebar et al, 2016), and habit and conscious intentions typically contribute about equal variance to PA under ordinary circumstances (Gardner, de Bruijn, & Lally, 2011;Rebar et al, 2016), it seems that the radically different context presented during the lockdown required more conscious decision making and interrupted routines. From a habit conceptualization, this is entirely sensible as habits are behavioural responses brought about by cues (Gardner, & Rebar, 2019;Rhodes, & Rebar, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, automatic motivation was negatively associated with both PA for transport and PA at work and not associated with the other PA modalities. Though automatic processes can be influential on PA (Di Maio, Keller, Hohl, Schwarzer, & Knoll, 2020;Kaushal, Rhodes, Meldrum, & Spence, 2017;Rebar et al, 2016), and habit and conscious intentions typically contribute about equal variance to PA under ordinary circumstances (Gardner, de Bruijn, & Lally, 2011;Rebar et al, 2016), it seems that the radically different context presented during the lockdown required more conscious decision making and interrupted routines. From a habit conceptualization, this is entirely sensible as habits are behavioural responses brought about by cues (Gardner, & Rebar, 2019;Rhodes, & Rebar, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on the public's infection prevention behaviors during the COVID-19 pandemic, Lin et al [32] reported that action self-efficacy influenced behavior through intention. Di Maio et al [33] also reported that action self-efficacy affected physical activity planning, while Kim and Yun [23] reported that self-efficacy positively affects health-promoting behaviors.…”
Section: Self-efficacy For Infection Prevention and Prevention Behaviorsmentioning
confidence: 99%
“…These studies among students [ 35 , 36 ] suggest that self-regulation interventions have a greater impact on those with lower habit strength compared to those with higher habit strength. Another study using a sample of adults, however, reported a null result for the moderating role of habit strength in the effect of planning intervention on physical activity behavior change [ 37 ]. More extensive research among various populations is needed to evaluate the moderating role of habit strength in self-regulation interventions.…”
Section: Introductionmentioning
confidence: 99%